Harmonization of Science and Ethics in Creating Learning Oriented Towards the Improvement of Student Character - Yuyung, Andi; Kamaruddin, Syamsu; Sinring, Abdullah; Lutfi, Lutfi (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2024)
This research aims to explore how the harmonization between science and ethics can be applied in the learning process to enhance students' character, with a focus on the challenges faced in integrating both aspects. Through a qualitative approach using the literature review method, this research identifies effective practices that support character-oriented learning. The findings show that the integrative application of science and ethics in learning not only enhances students' academic mastery but also strengthens their moral and social values. The significance of these findings for the development of holistic education, which not only pursues cognitive intelligence but also the formation of strong character, thereby creating a more responsible and ethical generation. Furthermore, the implications of this study emphasize the need for reforms in the education system that integrate ethical and scientific aspects, which are expected to improve the quality of education and prepare students to face global challenges.